Foliar fertilizers rarely increase yield in United States soybean. (27th October 2021) - Matcham, Emma G.; Vann, R. Atwell; Lindsey, Laura E.; Gaska, John M.; Lilley, Dylan T.; Ross, W. Jeremy; Wright, David L.; Knott, Carrie; Lee, Chad D.; Moseley, David; Singh, Maninder; Naeve, Seth; et al.
Abstract: Farmers have been interested in using foliar‐applied nutrient products to increase soybean [ Glycine max (L.) Merr.] yield since at least the 1970s, despite limited evidence that these products offer consistent yield increases when used prophylactically. Recently, interest in foliar fertilizer products for soybean production has been renewed, likely related to elevated soybean prices. Over the 2019 and 2020 growing seasons (46 site‐years), agronomists in 16 states collaborated to test six foliar nutrient treatments (commercial mixtures of macro‐ and micro‐nutrients) on soybean grain yield and composition. Soybean grain yield and composition differed among sites but not among foliar fertilizer treatments. Results show that prophylactic foliar fertilization is likely to decrease the profitability of soybean production. Foliar fertilizer products tested in this study and similar products should not be recommended to U.S. soybean farmers in the absence of visual symptoms of nutrient deficiency. Core Ideas: The tested prophylactic foliar fertilizers did not increase soybean yield. Foliar fertilizers did not change grain composition. Prophylactic foliar fertilizers tested decreased profitability.